Novel treatment of endobronchial inflammatory myofibroblastic tumor in a child. Issue 1 (28th October 2021) - Reyes‐Angel, Jessica; Rapkin, Louis B.; Simons, Jeffrey P.; Muzumdar, Hiren
Abstract: Isolated endobronchial inflammatory myofibroblastic tumors (IMT) are rare, accounting for about 1% of primary endobronchial tumors in children. The mainstay of treatment for this tumor has been surgical resection. Recently, the identification of anaplastic lymphoma kinase (ALK) gene mutations in half of IMTs and promising results of treatment with ALK inhibitors in other ALK‐positive tumors have opened the possibility of alternative approaches. We present a 4‐year‐old child with an ALK‐positive endobronchial IMT, treated with endoscopic resection and neoadjuvant therapy with crizotinib, without evidence of tumor recurrence 2 years after the initial resection.